Study on the macro and micro characteristics of the influence of deviator stress on true triaxial unloading failure - Jie Lai; Yuan Liu; Yu Cong; Yun Liu (Scientific Reports)
Abstract This paper uses a specific underground tunnel project in the eastern coastal region of China as its research background. It analyzes the impact of deviatoric stress on the evolution of rock unloading failure, providing data to support the understanding of dynamic failure during the excavation and construction of underground chambers. The macroscopic characteristics observed in true triaxial compression tests with confining pressure unloading revealed that during unloading, the ε1 curve initially dropped before rising back along the original loading path. In contrast, the ε2 and ε3 curves exhibited a vertical drop during unloading, followed by an increase. When the minimum principal stress was held constant, an increase in deviator stress resulted in higher peak stress and axial deformation. During the unloading failure process, crack development was primarily concentrated in the σ2 direction, while splitting and volumetric expansion were predominantly observed in the σ3 direction. As deviator stress increased, the number of cracks also rose, eventually leading to the formation of a “V”-shaped failure pattern characterized by significant rock spalling on the surface. The energy characteristics of the unloading failure tests indicated that the curve of elastic strain energy during unloading closely resembled the axial stress-strain curve. Furthermore, the increase in elastic strain energy was found to correlate with changes in axial stress. The findings provided valuable data to support understanding dynamic failure during the excavation and construction of underground chambers.